A novel method for the rapid detection of post-translationally modified visinin-like protein 1 in rat models of brain injury. (23rd February 2018) - Bradley-Whitman, Melissa A.; Roberts, Kelly N.; Abner, Erin L.; Scheff, Stephen W.; Lynn, Bert C.; Lovell, Mark A.
ABSTRACT: Background : Although elevated serum levels of visinin-like protein 1 (VILIP-1), a neuron-specific calcium sensor protein, are associated with ischaemic stroke, only a single study has evaluated VILIP-1 as a biomarker of traumatic brain injury (TBI). The current proof-of-concept study was designed to determine whether serum VILIP-1 levels increase post-injury in a well-characterized rat unilateral cortical contusion model. Methods : Lateral flow devices (LFDs) rapidly (< 20 min) detected trace serum levels (pg/mL) of VILIP-1 in a small input sample volume (10 µL). Temporal profiles of serum levels at baseline and post-injury were measured in male Sprague Dawley rats subjected to very mild-, mild unilateral-cortical contusion, or naïve surgery and in male Sprague Dawley rats following a diffuse TBI or sham surgery. Results : Mean serum levels were significantly elevated by 0.5 h post-injury and remained so throughout the temporal profile compared with baseline in very mild and mild unilateral contusions but not in naïve surgeries. Serum levels were also elevated in a small cohort of animals subjected to a diffuse TBI injury. Conclusions : Overall, the current study demonstrates that the novel LFD is a reliable and rapid point-of-care diagnostic for the detection and quantification of serum levels of UB-VILIP-1 in a clinically relevant time frame.